Nanorate sequencing reveals the Arabidopsis somatic mutation landscape - Cullan A. Meyer; Brad Nelms; Robert J. Schmitz (Proceedings of the National Academy of Sciences, 2025)
The rate and spectrum of somatic mutations can diverge from that of germline mutations. This is because somatic tissues experience different mutagenic processes than germline tissues. Here, we use nanorate sequencing (NanoSeq) to identify somatic mutations in Arabidopsis shoots with high sensitivity. We report a somatic mutation rate of 3.6 × 10 −8 mutations/bp, ~2 to 7× measured germline mutation rates. Somatic mutations displayed elevated signatures consistent with oxidative damage, UV damage, and transcription-coupled nucleotide excision repair. Both somatic and germline mutations were enriched in transposable elements and depleted in genes, but this depletion was greater in germline mutations. Somatic mutation rate correlated with proximity to the centromere, DNA methylation, chromatin accessibility, and gene/TE content, properties which were also largely true of germline mutations. We note that DNA methylation and chromatin accessibility have different predicted effects on mutation rate for genic and nongenic regions; DNA methylation associates with a greater increase in mutation rate when in nongenic regions, and accessible chromatin associates with a lower mutation rate in nongenic regions but a higher mutation rate in genic regions. Together, these results characterize key differences and similarities in the genomic distribution of somatic and germline mutations.